[Research on the Roman Historian Livy, Review of Ovid's Metamorphoses] - Solodow, Joseph B. (Spring;Foreign Language., 1999)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Translation of two 20th century plays] - Vena, Michael (1995)
Keywords: dept.wll; faculty_collection; sabbatical_report

Study of Oral Tradition in the Work of Mariano Baselgu Ramirez. - Garcia-Abrines, Maria (1991)
Keywords: dept.wll; faculty_collection; sabbatical_report

Experience in the Visions of Hildegarde Von Bingen. - Brockhagen, Marga (1989)
Keywords: dept.wll; faculty_collection; sabbatical_report

Critique of a Play of Victor Hugo. - Ecklund, Constance (1989)
Keywords: dept.wll; faculty_collection

Esa Lluvia De Fuego Que Nos Quema. - Gaeda, Rita (1988)
Keywords: dept.wll; faculty_collection; sabbatical_report

Poemas de New England - Geada, Rita (Indian Hill Press, 1996)
Keywords: Poetry.; dept.wll; faculty_collection

Offprint of Italian Literature: Roots and Branches: Essays in Honor of Thomas Goddard Bergin - Bergin, Thomas Goddard; Rimanelli, Giose; Atchity, Kenneth John (Yale University Press, 1976)
Vena, Michael. Alberti's linguistic innovations.
Keywords: dept.wll; faculty_collection

The Importance of the Spanish Language for North Americans - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: Spanish language; United States; dept.wll; faculty_collection

The Spanish and Spanish-American Novel - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: History and criticism; History and criticism; Spanish American fiction; Spanish fiction; dept.wll; faculty_collection

Intermediate German. - Werba, Henry (Holt, Rinehart and Winston, 1971)
Keywords: English; German language; Textbooks for foreign speakers; dept.wll; faculty_collection

Marcel Aymé et le Merveilleux. - Dumont, Jean-Louis (Debresse, 1970)
Keywords: Aymé; Marcel; 1902-1967; Marvelous; The; in literature; dept.wll; faculty_collection

Children, Schools, and Inequality - Entwisle, Doris R.; Alexander, Karl L.; Olson, Linda Steffel (Westview Press, 1997)
Keywords: Baltimore; Education; Elementary; Longitudinal studies; Longitudinal studies; Education; Elementary; Longitudinal studies; Educational equalization; Longitudinal studies; Observation (Educational method); Maryland; Social aspects; dept.wll; faculty_collection

Dictionary of Twentieth-Century Cuban Literature - Martínez, Julio A. (Greenwood Press, 1990)
Keywords: 20th century; Bio-bibliography; Cuban literature; Dictionaries; Dictionaries; Cuban literature; History and criticism; dept.wll; faculty_collection

French accent through video analysis - Ecklund, Constance L; Wiese, Peter (Foreign Language Annals, 1981)
Abstract Evaluating a student's accent in a foreign language is a complex process. Although it is obvious to the instructor whether or not the sound is correct, it is difficult for students both to hear the incorrect sound and to correct it. Too often the instructor merely tells the students that they have spoken incorrectly, expresses the sound properly, and then tries, often without lasting success, to have the students imitate. In a phonetically oriented course, diagrams are used as visual aids to teach correct articulation; but, especially at lower levels, it is difficult and often uninspiring for students to identify their speech production with such text figures. In a new method an improvised television “studio” captures the individual student's speech in an easily reviewable, permanent form on videotape. This visual, personal approach can make spectacular improvement in pronunciation, and the technique appears to be adaptable to any level of language learning. © 1981 American Council on the Teaching of Foreign Languages
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-131-487-553-974 tex.type: [object Object]
Keywords: dept.wll